Physicochemical properties changes on palm oil waste torrefaction : effect of temperature and residence time - Thor, Kait Wei (2017)
As a second largest palm oil exporter, utilization of palm oil biomass in Malaysia as the main renewable energy source is encouraged. To make the palm oil biomass more competitive with conventional energy source like coal, torrefaction pre-treatment was applied on the palm oil wastes which were palm kernel shell (PKS) and palm mesocrap fiber (PMF). The palm oil biomass were torrefied in a torrefaction reactor at different final temperatures of 240 °C, 270 °C, 300 °C, and 330 °C with different residence time of 30 min and 60 min in an inert condition. The change of the properties of the torrefied biomass include physical appearance, morphology structure, CHNS mass fraction, higher heating value (HHV), proximate analysis, and mass and energy yield. The physical appearance of torrefied biomass showed darken colour with higher torrefaction temperature. In term of morphological structure, SEM image revealed that severe torrefaction had more severe impact on the surface structure of PKS and PMF. Besides that, this study also reported that carbon mass fraction and higher heating value (HHV) increase with the increase of torrefaction temperature, but H/C ratio decreases for all torrefied biomass. Among the torrefied products, PKS had the highest carbon mass fraction of 59.9% and PMF had the highest HHV of 22.91 MJ kg-1. In terms of energy yield, PMF produced 90 – 95% yield and PKS produced 78 – 96% yield when torrefied from 240 °C to 330 °C for 30 min. In addition, the non-condensable gases released during torrefaction reaction include CH4, CO and CO2. This study concluded that the biomass had a lot of improvement such as improve in the grindability, higher energy density torrefied products, reduce moisture content and released volatile gases that can used as energy sources through torrefaction treatment.